Cost Analysis of Lymphadenectomy and Lymphedema One Year after Surgery for Endometrial Cancer: A Prospective Longitudinal Observational Multicenter Study - Madelene Wedin; Thomas Davidson; Evelyn Lundin; Karin Stålberg; Janusz Marcickiewicz; Gabriel Lindahl; Ninnie Borendal Wodlin; Preben Kjølhede (Clinical and Experimental Obstetrics & Gynecology)
Background: Since the therapeutic effect of lymphadenectomy on long-term survival in endometrial cancer treatment is disputed, a health economic evaluation of lymphadenectomy is important. The primary aim was to evaluate the direct hospital-related and health care-related costs of lymphadenectomy one year after surgery for endometrial cancer. A secondary aim was to evaluate the costs for lymphedema. Methods: This was a prospective longitudinal observational multicenter study. Fifteen Swedish hospitals participated: four university, seven central and four county hospitals. Women with presumed early-stage endometrial cancer assigned for primary surgery were eligible for the study. Between June 2014 and January 2018, 116 women, categorized as having high-risk endometrial cancer, underwent surgery with lymphadenectomy, and 119 categorized as having low-risk endometrial cancer had surgery without lymphadenectomy. The calculations of costs followed the structure of a cost analysis. Results: Lymphadenectomy increased the total costs for surgery within one year after surgery compared with treatment without lymphadenectomy by 71%, (mean (standard deviation) 118,205 Swedish crowns (SEK) (43,116 SEK) vs. 70,451 SEK (31,138 SEK)). The total hospital costs for those who developed lymphedema were 25% higher than for those without lymphedema (115,099 SEK (44,593 SEK) vs. 91,793 SEK (44,062 SEK)). Conclusions: Lymphadenectomy in the treatment of endometrial cancer increased hospital costs significantly. The hospital costs for the primary treatment of endometrial cancer for those who developed lymphedema one year after surgery were moderately higher than for those who did not, mainly due to higher surgical costs for lymphadenectomy, more unplanned outpatient visits, and readmissions that required surgery. Clinical Trial registration: The study has been registered on https://classic.clinicaltrials.gov/ (registration number: NCT02115477).